Job displacement in Australia Evidence from the HILDA survey - Sila, Urban (OECD Economics Department Working Papers, 2019)
Australia has a dynamic labour market with high job turnover. According to the HILDA Survey data, about one-fifth of all employees separate from their job every year, and about one fifth of those are displaced workers - laid off for economic reasons. Using multivariate probit regression we find that men, older workers and workers with less than secondary education tend to be displaced more often. In certain industries, such as construction and manufacturing, the incidence of displacement has been higher over the last fifteen years. Workers with lower tenure and casual employees also face a higher probability of displacement. However, a very high proportion - close to 80% percent - of displaced workers find a new job within two years. Among certain groups of workers, the share finding new employment is significantly lower: women, older workers, and less educated workers, workers who had a casual job and part-time workers. However, not all groups search for a job after being displaced. We find evidence that women, older workers and workers in low-skilled occupations are quite likely to exit the labour force following displacement